Towards the New Abnormal - Rachev, Rumen (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Rumen Rachev Title (English): Towards the New Abnormal Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 104 Page Count: 1 Citation (English): Rumen Rachev, “Towards the New Abnormal,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 104.